EFFICACY, SAFETY, AND PATIENT OUTCOMES OF EMERGENCY TREATMENT WITH IV INSULIN-DEXTROSE IN PATIENTS WITH HYPERKALEMIA - ASHRAF, H; KHURRAM, F; ASHRAF, F (Biological and Clinical Sciences Research Journal, 2024)
Hyperkalemia is a potentially life-threatening condition often encountered in emergency settings. Insulin-dextrose infusion is a common treatment to rapidly lower serum potassium levels, but this approach carries risks, particularly related to glucose imbalances. Objective: To evaluate the efficacy, safety, and clinical outcomes of insulin-dextrose infusion in the emergency treatment of patients with hyperkalemia. Methods: This retrospective study was conducted in the Emergency Department of Shifa International Hospital Islamabad from June 2023 to June 2024. The study included 400 patients with recorded potassium levels. Patients were categorized into non-hyperkalemic (K+ <5.5 mmol/L) and hyperkalemic (K+ ≥ 5.5 mmol/L) groups. Hyperkalemic patients received an insulin-dextrose infusion consisting of an average of 10 units of Actrapid insulin and 50 milliliters of 50% dextrose. Clinical outcomes, including efficacy and safety, were compared between treated hyperkalemic patients and those with moderate-severe hyperkalemia who did not receive the treatment. Statistical analysis was performed using odds ratios (OR) and 95% confidence intervals (CI) to assess the association between treatment variables and outcomes. Results: Glucose imbalances were observed in 60% of patients treated with insulin, with 50% developing hyperglycemia and 20% experiencing hypoglycemia, including 5% with severe hypoglycemia six hours post-treatment. Factors significantly associated with hypoglycemia included multiple insulin doses (OR: 2.9, 95% CI: 2.0-3.9), chronic kidney disease (CKD) (OR: 1.3, 95% CI: 1.0-2.1), and baseline glucose levels below seven mmol/L (OR: 3.0, 95% CI: 2.2-4.2). Hypoglycemic patients had a higher risk of mortality (OR: 1.49, 95% CI: 1.11-2.11). ICU admission occurred in three patients treated with insulin, with a higher risk associated with multiple doses (OR: 1.8, 95% CI: 1.4-2.9) and insulin doses greater than ten units (OR: 5.3, 95% CI: 2.9-10). Conclusion: The use of insulin-dextrose infusion in the emergency management of hyperkalemia is associated with a significant risk of hypoglycemia, ICU admission, and prolonged hospital stay. These findings suggest the need for improved treatment protocols to enhance patient safety in emergency settings.